Advances in the Discovery of Efflux Pump Inhibitors as Novel Potentiators to Control Antimicrobial-Resistant Pathogens - Song Zhang; Jun Wang; Juhee Ahn (MDPI AG, 2023)
The excessive use of antibiotics has led to the emergence of multidrug-resistant (MDR) pathogens in clinical settings and food-producing animals, posing significant challenges to clinical management and food control. Over the past few decades, the discovery of antimicrobials has slowed down, leading to a lack of treatment options for clinical infectious diseases and foodborne illnesses. Given the increasing prevalence of antibiotic resistance and the limited availability of effective antibiotics, the discovery of novel antibiotic potentiators may prove useful for the treatment of bacterial infections. The application of antibiotics combined with antibiotic potentiators has demonstrated successful outcomes in bench-scale experiments and clinical settings. For instance, the use of efflux pump inhibitors (EPIs) in combination with antibiotics showed effective inhibition of MDR pathogens. Thus, this review aims to enable the possibility of using novel EPIs as potential adjuvants to effectively control MDR pathogens. Specifically, it provides a comprehensive summary of the advances in novel EPI discovery and the underlying mechanisms that restore antimicrobial activity. In addition, we also characterize plant-derived EPIs as novel potentiators. This review provides insights into current challenges and potential strategies for future advancements in fighting antibiotic resistance.